Tradisi Ada' sebagai Rekontekstualisasi Mastery Learning dalam Pembelajaran Kitab Kuning - Djuwairiyah Djuwairiyah; Asmuki Asmuki; Ahmad Kusyairi; Mohamad Aso Samsudin; Zainal Abidin; Hasanah Hasanah (Jurnal Multidisiplin Ibrahimy, 2026)
Research on Mastery Learning has predominantly been conducted in formal education, particularly in health professions education, leaving its application in Islamic boarding school traditions largely unexplored. This study aims to examine the implementation of Mastery Learning principles in the ada’ tradition at Sukorejo Islamic Boarding School and to identify its contribution to the development of mastery learning concepts. A qualitative case study design was employed. Data were collected through participant observation, in-depth interviews, and document analysis, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that the ada’ tradition embodies five essential components of Mastery Learning: maqra’-based instructional fragmentation through Cross-Disciplinary Chunking, interactive oral formative assessment, immediate feedback delivered by peer tutors, flexible remediation based on individual learning pace, and enrichment through the integration of Arabic grammar (nahwu and sharaf), jurisprudential practice, sharḥ, and ḥāshiyah. These findings demonstrate that the core principles of Mastery Learning remain applicable but are recontextualized within the epistemological and pedagogical traditions of pesantren. The study concludes that the ada’ tradition extends the implementation of Mastery Learning through authentic performance-based learning, peer-assisted tutoring, and in-depth textual interpretation, resulting in a multidimensional conception of mastery that goes beyond conventional score-based assessment.